UJI EFEKTIVITAS EKSTRAK ETANOL DARI KULIT PISANG KEPOK (Musa Paradisiaca) UNTUK PENYEMBUHAN LUKA SAYAT PADA TIKUS - bunga mari sembiring (Jurnal Penelitian Farmasi & Herbal, 2020)
Banana peel turns out to have many benefits, one of which is that it can be used to accelerate the wound healing process. Banana peel (Musa Paradisiaca L.) ripe yellow skin is rich in flavonoid compounds, as well as other phenolic compounds, besides containing a lot of carbohydrates, minerals such as potassium and sodium and cellulose. This study aims to determine the wound healing effect of cuts using the Ethanol Extract of Kepok Banana Skins in Rats. Determine the concentration of ethanol extract of Kepok banana peel which is the most effective in healing wound cuts in mice. Knowing a significant difference to the acceleration of wound healing between ethanol extracts of Kepok banana peel and betadin. Research methods conducted included characterization, effectiveness test of ethanol extract of Kepok banana peel, manufacture of extract by maceration using ethanol 96% solvent, test of effectiveness of ethanol extract of kepok banana peel on cut wounds in mice. Data analysis using SPSS is Anova One Way Test. From the results of this study the ethanol extract of Kepok banana peel can have an effect on wound healing in mice. Ethanol extract of Kepok banana peel is faster than betadin in healing wound cuts in mice. Ethanol extract of Kepok banana peel with a dose of 750 Mg / kg BW is the most effective in healing wound cuts in rats.